Engaging with British European policy being nice to a sceptic? - Martin Kremer; Roderick Parkes (Stiftung Wissenschaft und Politik (SWP), 2009)
Whether the Conservatives replace the current Labour government at the next general election or not, their European policy will affect the United Kingdom's readiness for constructive action in the European Union. The very public nature of Conservative wrangling over the Union is exacerbating the problem at the heart of British European policy, namely the unresolved tension between the UK's highly effective, low-key euro-pragmatism and the constant bouts of public euroscepticism that are likely to induce an ever-growing emphasis on narrow national interests. With high public expectations about the EU's capacity to act under the new Lisbon Treaty, and with the new President of the Council and the High Representative yet to establish their reputations, member states must invest politically in the UK
Keywords: 320